Education on Cough and Cold Treatment with Acupressure Through Leaflets and Videos: Edukasi Penanganan Batuk Pilek dengan Akupresur Melalui Media Leaflet dan Video - Izzatus Sa'adah; Hesty Widowati (Academia Open, 2025)
Treatment of cough and cold is prioritized non-pharmacological. The purpose of this study was to determine differences in the level of knowledge and skills of mothers in handling cold coughs with acupressure through the media of leaflets and videos. The research method is Quasi Experimental Two Group Pretest Posttest. Population of mothers who have toddlers aged 1 to 5 years at Taman Sidoarjo Public Health Center. The Non Probability sample of 40 people was divided into two groups of leaflets and videos. The pretest uses a questionnaire for knowledge level and a checklist for mother's skills. Posttest one week after getting the intervention. The results of the research data were analyzed by the Independent T-Test test. The results of pretest leafleat knowledge 74.50 video 78.00 posttest leafleat 84.00 video 90.50 for pretest leafleat and video skills .00 posttest leafleat 11.743 video 9.787. The results of the T-Test test showed a p value > 0.05, so education on treating cold coughs with acupressure using leaflet and video media provided an increase in knowledge and skills, there was a difference in improvement, but the difference was not significant.